MATH SOLVE

4 months ago

Q:
# simplify −6(3i)(−2i) and 2(3 − i)(−2 + 4i) show work please

Accepted Solution

A:

i^2 = -1

-6(3i) = -18i

-18i(-2i) = 36(i^2)

36(i^2) = 36(-1)

36(-1) = -36

i^2 = -1

2(3 - i)(-2 + 4i) :(do foil)

2(-6 + 12i +2i - 4i^2)

-2 (-6 + 14i +4)

-2(-2 + 14i)

4 -28i

4-28i is your answer

hope this helps

-6(3i) = -18i

-18i(-2i) = 36(i^2)

36(i^2) = 36(-1)

36(-1) = -36

i^2 = -1

2(3 - i)(-2 + 4i) :(do foil)

2(-6 + 12i +2i - 4i^2)

-2 (-6 + 14i +4)

-2(-2 + 14i)

4 -28i

4-28i is your answer

hope this helps